Capital Inflows and Industrial Performance in Nigeria: Including the Excluded - Adekunle, Ibrahim Ayoade; Ogunade, Ayomide Olayinka; Kalejaiye, Toluwani Grace; Balogun, Adewale Musliudeen (Universitas Muhammadiyah Yogyakarta, 2020)
Africa most populous black nations remain underdeveloped, mainly due to shambolic industrial sector performance. Rising problems of insecurity, corrupt practices, consumerism structure have made gains from capital inflows minimal. Little is empirical credence has been leaned to the capital inflow-industrial output growth relationship in Nigeria. This anomaly has resulted in shortsighted policy formulation and attendant consequences. This paper examined international capital flows and industrial performance in Nigeria. The paper employed the two-step Engle and Granger estimation procedure and the Granger Causality to estimates parameters of the indices of industrial output growth and capital inflows to Nigeria. Findings revealed that labour participation, gross fixed capital formation, foreign direct investment (FDI) and portfolio investment have a significant positive relationship with industrial performance in Nigeria. Findings also revealed unidirectional causality from labour participation, gross fixed capital formation, foreign direct investment (FDI) and portfolio investment to industrial performance in Nigeria. Based on the findings, the Nigerian government should create an enabling environment to attract more capital inflow that could augment domestic resources with the sole aim of growing the industrial sector.